Clinical Anatomy and Imaging of the Cranial Nerves and Skull Base - Jha, Ruchira M.; Klein, Joshua P. (Seminars in Neurology, 2012)
Evaluation of patients with cranial neuropathies requires an understanding of brainstem anatomy and nerve pathways. Advances in neuroimaging, particularly high spatial resolution magnetic resonance imaging (MRI), have enabled visualization of these tiny structures and their related pathology. This review provides an approach toward using imaging in the evaluation of cranial nerve (CN) and skull base anatomy and pathology. Because brainstem nuclei are inextricably linked to the information contained within CNs, they are briefly mentioned whenever relevant; however, a comprehensive discussion of brainstem syndromes is beyond the scope of this review.
Keywords: cranial nerve; brain stem; skull base; steady-state free precession (SSFP)